Effectiveness of Diluent Gases on Hydrogen Flame Propagation in Tee Pipe(part II) – Influence of Tee Junction Position - Sina Davazdah, Emami; Rafiziana, Md. Kasmani; Zahra, Naserzadeh; Che Rosmani, Che Hassan; Mahar Diana, Hamid; Siti Zubaidah, Sulaiman; Norazana, Ibrahim; Mohd Dinie Muhaimin, Samsudin (Elsevier Ltd, 2017)
Gas explosions in obstructed vessels have been investigated for many years. However, the flame acceleration mechanism of enriched-hydrogen fuels with diluents in the piping system has received little systematic study in the literature. This particular study aimed to analyse the flame front mechanism of hydrogen-diluents/air explosion inside the pipe by considering the influence of tee junction distance from the ignition points. The tests were performed using H2/diluents-air at different concentrations and ignition positions, in two different tee junction pipe configurations. From the results, the worst case of explosion severity was found in 95% H2–2.5% Ar–2.5% N2/air for all ignition positions. In general, if ignition happened at the tee junction, the overpressure and rate of pressure rise profiles showed almost a similar trend on both configurations. Similar trend was also observed for the flame flow characteristic analysis. Overall, it was clearly demonstrated that a shorter distance between ignition point and obstacles resulted in higher explosion severity.